Academia - industry collaboration in translational medicine - Davie, N (2016)
Collaboration between academia and industry has been the focus of numerous government reports and initiatives over the past 15 years, and is increasingly recognized as an effective way to capitalize on the UK's world-class research base. However, there is a need to further understand the role of such collaborations in the field of translational medicine, where the path to market is particularly lengthy, expensive, and risky, due to complexities associated with the clinical trial process. This research uses a mixed methods approach to investigate collaboration in translational medicine at the University of Oxford. The project comprises three principal stages. First, a broad understanding of the current landscape of academia-industry collaboration in translational medicine was obtained by administering a questionnaire to academics who had received industry funding. Next, a deeper understanding of the barriers to collaboration was sought through semi-structured interviews with 27 academics. Finally, potential strategies to reduce practical barriers to the collaboration process were investigated through interviews with members of three groups within the university who interact directly with industry: Research Services, Oxford University Innovation, and Business Development. This research constitutes the first empirical study on university-industry collaboration in translational research in the United Kingdom. It contributes to existing theory through the development of a new theoretical framework for the evaluation of barriers in terms of a) the practicalities of the collaboration process, b) the institutional environment and c) presiding cultures. Through these analyses, differences in experiences of barriers to collaboration emerged for clinical and non-clinical researchers. Furthermore, industry was seen as playing a crucial role in the translation of new therapeutics, especially in the funding of research that was perceived as being ‘too risky’ for Research Councils. Thus, reducing barriers to university-industry collaboration was seen as important to the realisation of public benefit from university research. Barriers were seen as being overcome, or avoided, via the formation of relationships between academics and companies at several different levels; while systems exist within the university to facilitate this, awareness and uptake of these systems was poor amongst the study population. Finally, if universities are to deliver impact as a key metric of performance, incentives within the university need to reward academics for commercialisation activities, in addition to publication. Through the suggestion of long and short-term strategies and a detailed analysis of industrial collaboration in this setting, this research has implications for both university and government policy.